Evaluasi performa struktur bangunan eksisting terhadap beban gempa Zona 1 dan Zona 2 di Kabupaten Kotawaringin Timur - Ridho Saleh Silaban (Fakultas Teknik Sipil dan Perencanaan, 2026)
Based on the seismic hazard map of SNI 1726:2019, East Kotawaringin Regency is classified as a Zone-1 region with relatively very low seismic potential. However, an earthquake with a magnitude of approximately 4.5 occurred on 30 October 2023, indicating the possible need to reassess the regional seismic hazard classification from Zone-1 to Zone-2. This study aims to evaluate the structural performance of existing buildings under seismic loads corresponding to Zone-1 and Zone-2 conditions in accordance with SNI 1726:2019. The analysis results indicate that the total dynamic base shear of all buildings exceeds 85% of the total static base shear, satisfying the seismic design requirements. Interstorey drift evaluation shows that all buildings meet the allowable limits under Zone-1 seismic loading, whereas under Zone-2 loading, one building does not satisfy the drift requirement, representing 6.66% of the total buildings analyzed. The mass participation ratios in the principal seismic directions exceed 90%, confirming that the number of vibration modes considered is sufficient to represent the dynamic behavior of the structures. The increase in seismic demand from Zone-1 to Zone-2 results in a relatively small increase in axial forces in columns of 0.93%, while significant increases are observed in shear forces and bending moments, with column shear forces increasing by 12.48% in the x-direction and 11.24% in the y-direction, and bending moments increasing by 12.98% in the x-direction and 11.09% in the y-direction. For beam elements, shear forces increase by 3.82% and bending moments by 4.87%. The structural performance evaluation shows that the average ratio of nominal capacity to ultimate demand increases from 0.65 under Zone-1 conditions to 0.70 under Zone-2 conditions, corresponding to an increase of 8.49%. Furthermore, three buildings are classified as unsafe, accounting for 20% of the total buildings evaluated.